Knowledge and Skills Competencies for the Undergraduate Internal Medicine Curriculum in Saudi Arabia - Hani Almoallim (Association of American Medical Colleges, 2010)
Abstract This resource contains all of the research used to reconstruct the internal medicine curriculum in at Umm Alqura University in Saudi Arabia. This research can also assist in designing a national guide for internal medicine teaching in medical colleges of Saudi Arabia. It also can be used in designing a clerkship curriculum in internal medicine based on these specified competencies that augment and serve as a continuum of what had been taught in undergraduate curriculum. In this national research project, the knowledge and skills competencies in internal medicine for the undergraduate curriculum were determined and prioritized following a strict research methodology. A group of 20 clinicians rated the identified competencies from 0-3 (0: no need to know, 1: Interesting to Know, 2: Should Know and 3: Must Know). A total of 1514 knowledge competencies and 189 skills competencies were determined and prioritized. The competencies corresponded to 12 systems in internal medicine. This resource was used along with other work from different disciplines, at the institution to design an integrated curriculum where basic scientists and clinicians are sharing the same responsibilities in teaching medicine. This approach will greatly enhance the relevancy of the taught materials to the needs of medical students. The use of this resource should help in determining and specifying clear competencies for courses, curricula, lectures, problem-based learning, and bedside teaching sessions. It can also assist in the design of integrated curriculum that will greatly enhance the relevancy of the taught materials to the needs of medical students.